If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 11 = 5x + 15 Reorder the terms: 11 + 7x = 5x + 15 Reorder the terms: 11 + 7x = 15 + 5x Solving 11 + 7x = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 11 + 7x + -5x = 15 + 5x + -5x Combine like terms: 7x + -5x = 2x 11 + 2x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 11 + 2x = 15 + 0 11 + 2x = 15 Add '-11' to each side of the equation. 11 + -11 + 2x = 15 + -11 Combine like terms: 11 + -11 = 0 0 + 2x = 15 + -11 2x = 15 + -11 Combine like terms: 15 + -11 = 4 2x = 4 Divide each side by '2'. x = 2 Simplifying x = 2
| 3x*2+6x=9 | | 9x+229=4x+129 | | 3e/5=3 | | (3x-6)/(2x-2) | | -2+32=x+14 | | 16=x/6-8 | | x^^2/3=16 | | 8b+4=3 | | ln(x)=4.1+ln(7.9) | | 5x-17=4c+36 | | 1/3t-9=40 | | 3x(x-5)-7x^2+16x=0 | | 3n+13=4 | | t/5-2=10 | | log(-5x)=log(4x-9) | | 5x+5+x=77 | | log-5x=log(4x-9) | | 4x+2(4x-3)=138 | | K^2-3k-2=0 | | p(5)=3x^2+5x-4 | | 5x+9-4x=16 | | Y=ax-C | | 2(n-7)+3= | | 4f+8=8f-12 | | 2x-8x[9-4(x+3)]= | | 16t^2+12t^3=t^5 | | (6x+12)+(9x-4)= | | 50=7x-1 | | 4x+2+3x=2 | | -120-7+-120=-4([8*-10]+7)-11([-4*-10])+9 | | Pt-M^2t=P | | 3(4x-1)+2=2(2x-3) |